Reorganização da assistência de enfermagem no processo do parto e nascimento no HUPAA: enfoque na implantação do acolhimento ao recém-nascido no alojamento conjunto pela equipe de enfermagem - Juliana Nunes Lacerda (2017)
In Brazil, the Joint Housing System (SAC) is the assistance model adopted sea the care of the motherchild binomial. The joint accommodation las a place where the woman and the healthy newborn, soon after birth, remain together in up te lo full equipo. Reception is a practice present in all relationships of care, in real meetings between health workers and users, in the acts of receiving and listening te lo the people. The activity was performed in the joint housing of the Maternity Professor Mariano Teixeira, in at Hospital Universitário Professor Alberto Antunes Maceió-AL. where newborns were referred without prior passage, and care for the newborn was restricted to bathing, weight, medication administration, phototherapy, capillary glucose testing and breastfeeding promotion. To change this scenario I went in search of practical and scientific knowledge, which I was provided with through the Specialization in Obstetric Nursing by the Federal University of Minas Gerais in partnership with Federal University of Alagoas Objectives: Remodel nursing care in process of birth and delivery HUPPA, Maceió-AL; to implant the newborn in the joint accommodation; Implement service flow; promote continuity of care for the newborn, te lo promote the work of Nurses, offering technical-scientific subsidies sea their work; te lo promote discussion and reflection on the importance of the newborn's hospitalization. Methodology: after the Research Methodology module II, with the accomplishment of the situational diagnosis of the maternity, the need for intervention was identified, discussions were held together with the other CEEO II specializons filled in the joint accommodation. The development process was carried out through the communication and search of prior authorization of the Division of Nursing and nursing chief of the Emergency and Emergency sector, where the objectives of the project were explained and how it would be given its stages. The next step was the meeting with the nursing team with the purpose of sensitizing them to the importance of welcoming the newborn, as well as listening for suggestions to improve it. At another time, nurses from the pre-delivery, from the obstetrics center, ICU and from the ICU, the need for a shift to better care of the newborn were discussed. An approach was also carried out with small groups of the interdisciplinary team. The material used in the meetings was Administrative Rule 2068 of October 21, 2016. this is an intervention project with the host practices performed at the maternity Mariano Teixeira in at Hospital Professor Alberto Antunes in Maceió-AL, with participation of multiprofessional team crowded in the joint accommodation. The research during its implementation reached the objectives proposed in the study, because it had a theoretical support appropriate te lo the practice, creating discourses with the bosses, interaction with the other professions, and with the other sectors of the maternity which led te lo the strengthening of the assistance humanization of the newborn, increase of the indacadores of the screening tests and the reduction of emergency episodes. The research throughout the implantation reached the objectives proposed in the study, since it had adequate support te lo the practice, creating discussions with the heads, interaction with the other professions, and with the other sectors of the maternity, which led te lo the strengthening of the reception te lo the newly increased the indicators of screening tests and the reduction of emergency episodes. There was also the adhesion of all nursing staff in the other sectors on the importance of the shift from admission te lo admission te lo Newborn in ALCON, las well las the adherence of ALCON's full-equipo nursing team te lo the daily performance and when necessary of the evolution and annotation of nursing of Newborn.